Строговы: роман / Георгий Марков - Марков Георгий Мокеевич (Сибириада, 2022)
Экземпляры: ф.15 (20230418) / Инвентарный номер: 63385 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 27 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44